ANALISA DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PG ASEMBAGOES DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Syarifa, Lailatus; Karnadi, Karnadi; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The results of the hypothesis testing using the Smart PLS 3.0 application indicate that directly, work discipline has a significantly positive influence on job satisfaction, the work environment has a significantly positive influence on job satisfaction, work discipline has a positive but not significant influence on performance, the work environment has a positive but not significant influence on performance, and job satisfaction has a positive but not significant influence on performance. The results of the hypothesis testing for indirect effects show that the work discipline variable has a positive but not significant influence on performance through job satisfaction, and the work environment variable has a positive but not significant influence on performance through job satisfaction.